Romeo and Juliet - Shakespeare, William 1564-1616 (Shakespeare, William 1564-1616. No fear Shakespeare., 2003)
Presents the original text of Shakespeare's play side by side with a modern version, with marginal notes and explanations and full descriptions of each character.